Tax Amnesty Moderation: The Influence of Tax Knowledge and Sanctions on Taxpayer Compliance - Elva Anggreany; Estralita Trisnawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to explore the impact of taxpayers' understanding of tax regulations and the influence of fiscal penalties on the likelihood of compliance among individual taxpayers, with tax amnesty serving as a moderating variable at KPP Pratama Batam Selatan. The research focuses on a sample drawn from individual taxpayers (WPOP). registered at the South Batam Tax Office in 2023. The data harnessed in this research are derived from primary sources, meticulously procured via the dissemination of structured questionnaires to designated participants. The analysis was conducted using the SEM-PLS technique, implemented via SmartPLS version 3.0. The results confirm that both tax literacy and fiscal sanctions have a meaningful and statistically significant effect on the compliance behavior of individual taxpayers. Moreover, the study indicates that the implementation of tax amnesty plays a crucial role in enhancing the link between taxpayers' understanding of tax regulations and their adherence to tax obligations. Conversely, the results demonstrate that tax amnesty has no meaningful effect on how fiscal penalties impact taxpayers' compliance behavior.